CORRELATION OF HAEMOGLOBIN LEVEL WITH INTESTINAL PARASITES IN SCHOOL CHILDREN - Shah, Said Alam; Zai, Salar; Muhammad, Amir (Journal of Postgraduate Medical Institute, 2011)
Objective: To find out the pattern of parasitic infestation and its effect on hemoglobin level in school children at Hayatabad area of Peshawar. Material and Methods: Stool and blood samples from 230 school children in Hayatabad were collected during October, 2004 to May, 2005. The stool specimens were examined for parasites using normal saline and iodine, while haemoglobin was estimated by cyanomethemoglobin method in blood samples. Results: The overall infection rate was 29.1% (n=67/230), of which 6% (n=4/67) showed mixed infection. Among positive cases, Ascaris lumbricoides was the commonest (n=26; 38.8%), followed by Hymenolepis nana (n=18; 26.9%). Entamoeba coli was present in 10.4% (n=7) cases, Giardia lamblia in 9% cases and Entamoeba histolytica in 6% (n=4) cases. Taenia saginata and Enterobius vermicularis were present in 3% (n=2), while Trichuris trichiura and Hookworm each was found in 1.5% (n=1) cases. The mean haemoglobin in healthy subject was 13.6 g/dl, while in infected subjects it was 11.4 g/dl, the difference was statistically significant (p<0.05). Conclusion: The health status of the school children needs to be checked and worm infestation is a common problem in school going children.